Practical deliberation is normative - Hambly, Jesse (Journal of the American Philosophical Association, 2025)
It is common for philosophers to suggest that practical deliberation is normative; deliberation about what to do essentially involves employing normative concepts. This thesis—‘the Normativity Thesis’—is significant because, among other things, it supports the conclusion that normative thought is inescapable for us. In this article, I defend the Normativity Thesis against objections.
Gesehen am 09.02.2026